2021
DOI: 10.1371/journal.pone.0261566
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and prognosis of gastrointestinal stromal tumors containing air-fluid levels

Abstract: An air-fluid level within a gastrointestinal stromal tumor (GIST) is unusual and indicates the presence of a fistula within the lumen of the GI tract. Until recently, the optimal management of such patients was not clear-cut. This retrospective study investigated the clinicopathological characteristics, surgical procedures, pre-and post-operative management, and prognosis of patients with GIST containing an air-fluid level. Data of GIST patients, spanning 5 years, including 17 GIST patients with air-fluid leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Moreover, the clinical presentation of GISTs, such as an unclear tumor boundary, irregular tumor shape, and the presence of a gas-liquid interface in imaging scans, can indicate aggressive behavior and malignancy. Gas-liquid interface detection in GISTs is currently uncommon, but researchers believe that it predicts severe disease in GIST patients[ 25 - 27 ]. Our study found that necrosis and rupture were more likely to occur when an air-liquid interface was present, and these factors were important indicators of poor prognosis in GIST patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the clinical presentation of GISTs, such as an unclear tumor boundary, irregular tumor shape, and the presence of a gas-liquid interface in imaging scans, can indicate aggressive behavior and malignancy. Gas-liquid interface detection in GISTs is currently uncommon, but researchers believe that it predicts severe disease in GIST patients[ 25 - 27 ]. Our study found that necrosis and rupture were more likely to occur when an air-liquid interface was present, and these factors were important indicators of poor prognosis in GIST patients.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic evidence of fistulization may include the presence of air fluid levels within the suspected mass. 5 Despite being clinically asymptomatic, fistulization between the GIST and the intestinal lumen is important to recognize because it may serve as a conduit for bacterial translocation, leading to infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Жодна з схем для прогнозування ризику рецидиву або метастазування хірургічно видаленої первинної стромальної пухлини не передбачає чіткого поділу доброякісних і злоякісних СПШКТ [6,[26][27][28][29][30]. Експерти вважають за краще не використовувати слово «доброякісний» для будь-яких СПШКТ адже ж навіть дуже маленькі GIST з низьким потенціалом злоякісності рецидивують або метастазують через роки після хірургічної резекції.…”
unclassified